The guaranteed minimum income in Portugal: a universal safety net under political and financial pressure - Pereirinha, J. A.; Branco, F.; Pereira, E.; Amaro, M. I. (Social Policy and Administration, 2020)
The Guaranteed Minimum Income (GMI) was created in Portugal by a centre-left Socialist Party government in 1996, as the most important constitutive part of a ‘new generation of active social policies,’ which completed the existence in Portugal of a universal system of guaranteedincome. Its transformation into a Social Integration Income (SII) in 2003 and its retrenchment in the period of the Great Recession and troika austerity (2011–2015) has reduced the scope of this policy measure as a universal safety net policy. This article examines the context and the major drivers for the creation and for the policy changes that occurred in the GMI/SII. Looking at the political debates and the changes in this policy measure along this period, we argue that the major reforms introduced since its creation reflect ideological cleavages within the political arena. Considering the very low share in total government current expenditure of GMI/SII, this can explain the social policy selective retreat associated to the changes introduced in this policy measure by the centre-right coalition in government, in the latest period of cost containment of social policy in Portugal, leading to a great decrease in the number of beneficiaries and to an increase of its inadequacy.